The Devil's Mousetrap : Redemption and Colonial American Literature. - Munk, Linda (Oxford University Press, 1997)
This text explores the thought of three colonial New England divines - Increase Mather, Jonathan Edwards and Edward Taylor - from a literary theory perspective. The author focuses on the background of the men's ideas, exploring the construction of Puritan theology.